Accumulation or absorption? Changing disparities of household non-employment in Europe during the Great Recession. (14th February 2020) - Biegert, Thomas; Ebbinghaus, Bernhard
Abstract: This comparative study analyzes the impact of the Great Recession on household non-employment across Europe since 2008. We use the EU-SILC (2007–2014) for a shift-share analysis that decomposes annual variations in household non-employment in 30 European countries. Investigating whether job loss is absorbed by or accumulated in households, we break down non-employment variations into changes in individual non-employment, household compositions and polarization. We find that household joblessness increased since 2008, especially in crisis-ridden countries. There is no evidence for the widespread absorption of individual non-employment in families or multi-person households. Instead, household dynamics and unequal distribution of non-employment lead to further risk accumulation within households during the crisis. Surprisingly, this pattern occurs in those crisis-ridden countries known for their traditional household structures and less accommodating welfare systems, which have relied thus far on families to absorb employment risks. The Great Recession has aggravated household disparities in joblessness in Europe.